2023
DOI: 10.5194/nhess-23-2333-2023
|View full text |Cite
|
Sign up to set email alerts
|

Low-regret climate change adaptation in coastal megacities – evaluating large-scale flood protection and small-scale rainwater detention measures for Ho Chi Minh City, Vietnam

Abstract: Abstract. Urban flooding is a major challenge for many megacities in low-elevation coastal zones (LECZs), especially in Southeast Asia. In these regions, the effects of environmental stressors overlap with rapid urbanization, which significantly aggravates the hazard potential. Ho Chi Minh City (HCMC) in southern Vietnam is a prime example of this set of problems and therefore a suitable case study to apply the concept of low-regret disaster risk adaptation as defined by the Intergovernmental Panel on Climate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Quantitative assessment of climate change is vital for justifying mitigation strategies to restrain global warming and minimize adverse consequences (Ciscar et al, 2011; Maranzoni et al, 2022; Ranger et al, 2011). Scheiber et al (2022) applied flood protection and mitigation measures in the Ho Chi Minh City, Vietnam, and quantified the extent of flood damage reduction using the flood severity index as metrics. Likewise, the quantitative assessment of the effect of adaptation policies can serve as the basis for selecting and implementing policy priorities by decision‐makers (Hammond et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative assessment of climate change is vital for justifying mitigation strategies to restrain global warming and minimize adverse consequences (Ciscar et al, 2011; Maranzoni et al, 2022; Ranger et al, 2011). Scheiber et al (2022) applied flood protection and mitigation measures in the Ho Chi Minh City, Vietnam, and quantified the extent of flood damage reduction using the flood severity index as metrics. Likewise, the quantitative assessment of the effect of adaptation policies can serve as the basis for selecting and implementing policy priorities by decision‐makers (Hammond et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previously centrally run cities such as HCMC only included the administrative units of urban districts (quận) subdivided into wards (phường), with rural districts subdivided into communes (xã) and townships (thị trấn). In response, to accommodate the growing population, the city has reshaped its form and rapidly expanded, suburbanising industries and populations as well as constructing infrastructure, resulting in reduced green space, encroachment of fertile cropland and low-lying marshland, and an increased extent of sealed surfaces [56][57][58][59]. Xu et al (2019) reported that the urban built-up area of Greater HCMC increased over 10-fold from a mere 5500 ha in 1990 to 63,500 ha by the year 2013 [30].…”
Section: Introductionmentioning
confidence: 99%